Features and Barriers of Information Interaction between Authorities and Citizens Using E-democracy Technologies and Supply Chain Management at Municipal Level - Ekaterina A.Vetrova; Natalia V.Medvedeva; Elena E.Kabanova; Tatiana A.Evstratova; Lyudmila V.Senicheva (International Journal of Supply Chain Management, 2019)
The present paper discusses practical aspects of improving the efficiency of working with letters and appeals of citizens in local governments and supply chain management. The main difficulties of working with citizens’ letters and appeals in local governments in the Russian Federation have been studied; working with letters and appeals of citizens in the Administration of Dmitrovsky District of the Moscow Region has been analyzed and possible mechanisms have been proposed for increasing the efficiency of working with letters and appeals of citizens. The best practices in dealing with citizens’ appeals to an absolute degree illustrate the direct relationship between qualitative organization of the administrative-legal system for protection of the legal rights and freedoms of the population and executive branch. The timeliness and efficiency of decision-making regarding demands of the population undoubtedly characterizes any administrative apparatus to be the most competent and wealthy. As the level of trust in government, such an important aspect of modern society is mainly influenced by well-coordinated mechanisms for dealing with citizens’ appeals and reflected in congruence of the decisions made. Thus, the existence of two important functions of the institution of citizens’ appeal cannot be denied; the first of which is the ability of population to realize their rights, enshrined in the constitution; the second function is the direct participation of population in governing the state, also having a constitutional democratic basis.